Bioinformatic Analysis and in Vitro Validation of Let-7b and Let-7c in Breast Cancer. (February 2020) - Bozgeyik, Esra
Graphical Abstract: Highlights: Let-7b and let-7c were significantly altered in breast cancer Let-7b and let-7c significantly altered cancer-related gene expression Both miRNA might have crucial roles in breast cancer progression ABSTRACT: Members of the let-7 family of miRNAs are well-known with their tumor suppressor properties as they are expressed at low levels in several types of human malignancies. Among them, let-7b and let-7c have gained special attention due their broad significance. Although the role of let-7b and let-7c have been widely reported in various types of cancers, their functional importance and role in oncogenic signaling of breast cancer is poorly investigated. Therefore, in the present study, prognostic and diagnostic significance of let-7b and let-7c in breast cancer and the effects these miRNAs on genes involved in cancer progression were determined by using several bioinformatics analysis and validated in vitro mimic assays, respectively. Using data of TCGA, OncomiR and dbDEMC 2.0, overall expression analysis of let-7b and let-7c was performed. The effect of let-7b and let-7c on genes involved in cancer progression was investigated by mimic transfection assays. We found that both let-7b and let-7c were significantly altered in breast cancer and associated with the clinicopathological findings of patients. Additionally, both let-7b and let-7c significantly altered oncogenic signaling in breast cancer cells. Consequently, both miRNAs might have fundamental roles in breast cancer progression and can be considered as potential targets for breast cancer therapy and diagnosis.